The role of concordant and discordant comorbidities on performance of self-care behaviors in adults with type 2 diabetes: a systematic review - Aga F (Dove Medical Press, 2019)
Fekadu Aga,1 Sandra B Dunbar,2 Tedla Kebede,3 Rebecca A Gary21Department of Nursing, School of Nursing & Midwifery, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Nell Hodgson Woodruff School of Nursing, Emory University, Atlanta, GA 30322, USA; 3Tikur Anbessa Specialized Hospital, Diabetes & Endcrinology Unit, Department of Internal Medicine School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaBackground: Most patients with Type 2 diabetes (T2D) have high number of comorbid chronic conditions that can affect their self-care abilities. Guidelines for diabetes self-care behaviors are disease specific with little attention given to managing T2D with other comorbidities. Identifying comorbidities that either improve or potentially diminish the individual’s capacity to perform effective self-care behaviors is essential to enhance clinical outcomes. One such framework conceptualizes comorbidities as concordant or discordant with diabetes pathophysiological pathways and care goals.Objective: The purpose of this systematic review was to examine the role of diabetes-concordant and discordant chronic conditions on the performance of self-care behaviors in adults with T2D.Methods: A comprehensive literature search was undertaken to identify published English language articles through the following five electronic databases: PubMed, CINAHL, PsycINFO, ISI Web of Science, and EMBASE. Quantitative studies published from March 2006 to April 2018 were included. Quality of evidence was evaluated using the Joanna Briggs Institutes Critical Appraisal Tools (JBI-CAT) and rated using Quality Assessment Tool for Quantitative Studies (QATQS).Results: The initial database search identified 1,136 articles but only 33 studies that met the inclusion criteria were included. The most common concordant comorbidity was hypertension while depression was the most common discordant condition. Adherence to medications was the most frequent diabetes self-care behavior reported and tended to be higher among concordant comorbidities. The findings showed mixed results concerning the effect of some concordant comorbidities such as hypertension, hyperlipidemia, retinopathy, and heart failure on diabetes self-care behaviors. But, there is agreement across studies that diabetes-discordant comorbidities have a more detrimental effect on self-care behaviors.Conclusions: Concordant comorbidities may improve diabetes self-care, but the evidence is inconclusive. Future research using well designed studies are needed to examine the complex relationship between diabetes self-care and comorbidities.Keywords: comorbidity, concordant comorbidity, diabetes self-care behaviors, discordant comorbidity, multimorbidity, type 2 diabetes